Determinan Tingkat Pengangguran Terbuka pada 21 Daerah di Pulau Jawa - Arifah, Nur Laili; Prabowo, Prayudi Setiawan (Jurnal Ekonomika : INDEPENDEN, 2024)
Unemployment is a recurring issue in developing countries that can disrupt the labour sector. This study was conducted to understand the effect of Economic Growth, Population, and Human Development Index on Open Unemployment Rate in 21 Regions. Secondary data sourced from BPS from 2018-2022 was applied and tested with panel data regression analysis using E-Views 12. The test results show that partially, economic growth has a significant negative effect, population has no significant effect, and HDI has a significant positive effect on the open unemployment rate. Furthermore, simultaneously, economic growth, population, HDI affect the open unemployment rate in 21 regions in Java Island.